An effective CuO/Bi2WO6 heterostructured photocatalyst: Analyzing a charge-transfer mechanism for the enhanced visible-light-driven photocatalytic degradation of tetracycline and organic pollutants. (January 2022) - Koutavarapu, Ravindranadh; Syed, Kamaluddin; Pagidi, Srinivas; Jeon, Min Yong; Rao, M.C.; Lee, Dong-Yeon; Shim, Jaesool
Abstract: Over the past few years, industrial pollution has had a negative impact on aquatic life by releasing significant amounts of hazardous chemicals into the ecosystem. Therefore, it is imperative to develop photocatalytic materials with good photocatalytic activity and easy separation. Photocatalytic degradation has been employed for the removal of such contaminants using binary hybrid nanocomposites as photocatalysts. In the present study, binary CuO/Bi2 WO6 (CuBW) nanocomposites with different loadings of Bi2 WO6 ( 5, 10, and 15 mg) were successfully constructed using a simple hydrothermal method and used as a potential photocatalyst for the degradation of tetracycline (TC) and methylene blue (MB) under visible-light irradiation. The structure, surface morphology, and optical properties were studied to investigate the formation of the heterostructure. Among the prepared samples, the CuBW nanocomposite containing the optimum content of Bi2 WO6 ( 10 mg) exhibited superior activity toward the photocatalytic degradation of TC (97.72%) in 75 min and MB (99.43%) in 45 min under visible-light illumination. Radical trapping experiments suggested that holes and OH radicals were the dominant reactive species during the photocatalytic process. The photoelectrochemical results also confirmed the improved separation and transfer of electron-hole pairs at the interface of Bi2 WO6 and CuO. Our results demonstrate that the binary CuO/Bi2 WO6 nanocomposite has significant potential applications in the field of photocatalysis due to its enhanced separation of the photoexcited charge carriers and strong synergistic interactions. Graphical abstract: Image 1 Highlights: Hydrothermal method is used to prepare the CuO/Bi2 WO6 nanocomposite. Structural and morphology studies confirmed the formation of heterostructures. Loading of Bi2 WO6 nanoflakes over CuO nanorods improved the catalytic activity. The nanocomposite degraded 97.72% of TC and 99.43% of MB under visible light. Strong interfaces and charge separation improved the performance of CuO/Bi2 WO6 nanocomposite.